First next-generation sequencing full-genome characterization of a hepatitis C virus genotype 7 divergent subtype. (November 2016) - Salmona, M.; Caporossi, A.; Simmonds, P.; Thélu, M.-A.; Fusillier, K.; Mercier-Delarue, S.; De Castro, N.; LeGoff, J.; Chaix, M.-L.; François, O.; Simon, F.; Morand, P.; et al.
Abstract: We report the near-full-length genome sequence of a hepatitis C virus (HCV) isolate from a man originating from Democratic Republic of Congo, the genotype of which could not be determined by the routinely used sequencing technique. The near-complete genome sequence of this variant BAK1 was obtained by the association of two next-generation sequencing technologies. Evolutionary analysis indicates that this isolate, BAK1, could be the first reported strain belonging to a new HCV-7b subtype. This new subtype has been incorrectly identified as genotype 2 by the Versant HCV Genotype 2.0 assay (LiPA). The requirement of three independent isolates has been filled, and a new subtype can be assigned. More examples of HCV-7 are required to better understand its origin, its pathogenicity and its relationship with genotype 2.